Dysregulation of the suppressor of cytokine signalling 3–signal transducer and activator of transcription‐3 pathway in the aetiopathogenesis of Sjögren's syndrome. (September 2014) - Vartoukian, S. R.; Tilakaratne, W. M.; Seoudi, N.; Bombardieri, M.; Bergmeier, L.; Tappuni, A. R.; Fortune, F.
Summary The suppressor of cytokine signalling 3 (SOCS3) negatively regulates the Janus kinase (JAK)/signal transducer and activator of transcription‐3 (STAT‐3)/interleukin (IL)‐17 pathway. The proinflammatory cytokine IL‐17 is over‐expressed in Sjögren's syndrome (SS) and is a key factor in its pathogenesis. We hypothesized that IL‐17 over‐expression in SS results from ineffective regulation by SOCS3. The expression of SOCS3 was analysed in peripheral blood mononuclear cells (PBMC) from SS cases, sicca controls (SC) and healthy controls (HC) and tissue samples from SS, SC and healthy salivary glands (HSG). PBMC and salivary gland tissue from SS and controls were dual‐immunostained for SOCS3 and IL‐17. IL‐6‐stimulated PBMC from SS and controls were evaluated for time‐dependent STAT‐3 activation and SOCS3 induction, and for IL‐17 expression. Immunoblotting revealed greater levels of SOCS3 in PBMC from SS than SC (P = 0·017) or HC (P < 0·001). Similarly, the proportion of salivary‐gland tissue cells staining for SOCS3 was significantly higher in SS than SC (P = 0·029) or HSG (P = 0·021). The cells in PBMC/salivary gland samples from controls predominantly expressed either SOCS3 or IL‐17. However, there was a high frequency of SOCS3/IL‐17 co‐expression within cells of SS samples. IL‐6‐stimulation of PBMC from SS cases revealed prolonged activation of STAT‐3 with reduced negative regulation by SOCS3, and enhanced expression of IL‐17. This study showed that SOCS3 expression is up‐regulated in SS. However, the absence in SS of the normal inverse relationship between SOCS3 and pSTAT‐3/IL‐17 indicates a functional disturbance in this signalling cascade. Consequently, a reduction in function, rather than a reduction in expression of SOCS3 accounts for the unregulated expression of IL‐17 in SS, and may play a crucial role in aetiopathogenesis.